Physicochemical characterization of phosphinic pseudopeptides by capillary zone electrophoresis in highly acidic background electrolytes - Koval, Dusan; Kasicka, Václav; Jirácek, Jirí; Collinsová, Michaela (Electrophoresis, 2003)
Phosphinic pseudopeptides (i.e., peptide isosteres with one peptide bond replaced by a phosphinic acid moiety) were analyzed and physicochemically characterized by capillary zone electrophoresis in the pH range of 1.1-3.2, employing phosphoric, phosphinic, oxalic and dichloroacetic acids as background electrolyte (BGE) constituents. The acid dissociation constant (pK(a)) of phosphinate group in phosphinic pseudopeptides and ionic mobilities of these analytes were determined from the pH dependence of their effective electrophoretic mobilities corrected to standard temperature and constant ionic strength of the BGEs. It was shown that these corrections are necessary whenever precise mobility data at very low pH are to be determined. Additionally, it was found that the ionic mobilities of the phosphinic pseudopeptides and pK(a) of their phosphinate group are affected by the BGE constituent used. The variability of migration behavior of the pseudopeptides can be attributed to their ion-pairing formation with the BGE components.
Keywords: pufry; Electrolytes; Temperature; matematika; kyselina dichloroctová; Electrophoresis, Capillary; Dichloroacetic Acid; kyselina oxalová; teplota; Mathematics; molekulární struktura; peptidy; osmolární koncentrace; elektroforéza kapilární; Molecular Structure; Peptides; kyseliny fosfinové; elektrolyty; Hydrogen-Ion Concentration; kyseliny fosforečné; koncentrace vodíkových iontů; Oxalic Acid; Phosphinic Acids; Osmolar Concentration; Phosphoric Acids; Buffers